2015
DOI: 10.1002/oby.20999
|View full text |Cite
|
Sign up to set email alerts
|

DBC1 is involved in adipocyte inflammation and is a possible marker of human adipose tissue senescence

Abstract: Objective: To investigate the possible role of deleted in breast cancer 1 (DBC1) in adipocyte and adipose tissue inflammation. Methods: In vitro knockdown experiments using shRNA-lentiviral particles were performed to investigate the effect of DBC1 on adipocyte inflammation, sirtuin 1 (Sirt1) activity, and the AMPK pathway. The relationship between DBC1 and inflammation in human adipose tissue also was examined in two independent cohorts. Results: Dbc1 knockdown (KD) led to a significant reduction in the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Of more clinical relevance, it has been shown that high-fat diet can reduce SIRT1 levels in white adipose by inflammatorymediated caspase 1 [144], and in turn, resveratrol supplementation in high-fat diet fed rhesus monkeys prevents adipose tissue inflammation [145]. Most recently, an inhibitor of SIRT1, deleted in breast cancer 1, was shown to be involved in regulating adipose tissue inflammation and adipose tissue senescence using deleted in breast cancer 1 knockout mice, and was shown to positively correlate with proinflammatory markers in both subcutaneous and visceral adipose tissue in morbidly obese [146]. Similarly, considerable research has shown that sirtuin function, most notably SIRT1 and SIRT6, is involved in regulating the inflammatory response in myeloid and lymphoid cells that can infiltrate the adipose tissue.…”
Section: Sirtuin Control Of Inflammationmentioning
confidence: 99%
“…Of more clinical relevance, it has been shown that high-fat diet can reduce SIRT1 levels in white adipose by inflammatorymediated caspase 1 [144], and in turn, resveratrol supplementation in high-fat diet fed rhesus monkeys prevents adipose tissue inflammation [145]. Most recently, an inhibitor of SIRT1, deleted in breast cancer 1, was shown to be involved in regulating adipose tissue inflammation and adipose tissue senescence using deleted in breast cancer 1 knockout mice, and was shown to positively correlate with proinflammatory markers in both subcutaneous and visceral adipose tissue in morbidly obese [146]. Similarly, considerable research has shown that sirtuin function, most notably SIRT1 and SIRT6, is involved in regulating the inflammatory response in myeloid and lymphoid cells that can infiltrate the adipose tissue.…”
Section: Sirtuin Control Of Inflammationmentioning
confidence: 99%
“…Increased TSH mRNA levels and circulating TSH were significantly associated with reduced markers of cellular senescence (including BAX, DBC1, TP53, TNF gene expression [12,13] and specific glucosylceramides [21,23]) and increased telomere length in both human and rat AT. These data agree with the positive association between serum TSH levels and longevity reported in rodents [1][2][3] and euthyroid humans [3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 97%
“…Adipose tissue cellular senescence is characterized by increased expression of apoptotic and senescence markers (caspase induction leading to increased BAX, TP53 and DBC1 expression), decreased telomere length [11][12][13][14][15], and impaired capacity to generate new adipocytes and mitochondrial dysfunction [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…We and others have extensively shown that DBC1 plays major roles in metabolism and metabolic diseases 19,22,[31][32][33][34][35] . DBC1 regulates SIRT1 activity in the liver and adipose tissue during different metabolic states 22,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Many lines of research support that DBC1 is involved in the control of metabolism and metabolic diseases 19,22,[31][32][33][34] . We also showed that DBC1 KO mice have increased SIRT1 activity in vivo in liver and they are protected against non-alcoholic fatty liver disease 22 .…”
mentioning
confidence: 99%